A Comparative Study between Endoscopic and Microscopic Tympanoplasty - Dhungana, Anup; Joshi, R. R.; Rijal, A. S.; Shrestha, K. K.; Maharjan, S. (Nepal Medical College Journal, 2019)
A study to compare tympanoplasty between endoscopic and microscopic approach was conducted at NMCTH. Patients diagnosed as chronic otitis media – mucosal type with age of 13 years and above were included in the study. Audiometric test was done before and 6 weeks after surgery. Seventy cases were included for the study with random allocation of cases each in endoscope group and microscopic group respectively. Graft uptake results were assessed after 6 weeks and postoperative hearing were evaluated and compared within and between the two groups. In endoscopic group and microscopic group, the graft uptake rate was 91.4% and 88.5% respectively with no significant difference (p = 0.71) in the graft uptake rate between the groups. The mean pre and post-operative air bone gap in endoscopic group and microscopic group were 34.59 dB±8.02, 21.97±8.60 dB and32.42±10.08 dB, 18.55±8.49 dB respectively. This showed a highly significant difference in both groups(p < 0.001), showing improvement in the hearing after surgery in both the groups. The mean air bone gain were 12.62 dB and 13.87 dB in endoscopic and microscopic group respectively, with no significant difference between the groups (p = 0.553). The graft uptake rate and hearing results with endoscopic technique is comparable to that of microscopic technique. However, the endoscopic technique requires shorter operative time than the microscopic technique. Therefore, we recommend the use of endoscope for tympanoplasty in hospital as well as in camps.